Perancangan dan Evaluasi Desain Antarmuka Pengguna pada E-Commerce Peralatan Medis Berbasis User Centered Design - Wardhanie, Ayouvi Poerna; Effendi, Pradita Maulidya; Prasetyo, Muhammad Farid Alif (Politeknik Harapan Bersama, 2025)
In today’s rapidly evolving digital era, e-commerce platforms play a key role in distributing information, marketing, ordering, and online product sales. However, many platforms still struggle with suboptimal user interface and user experience design, such as unclear product and company information, complex ordering and payment processes, and visually unappealing interfaces, such as layout, colour, images, and typography. This study aims to designing the UI/UX design of a healthcare e-commerce platform at PT. Wanbass Timur Persada is using the User Centered Design (UCD) approach. UCD emphasizes active user involvement throughout the design process to ensure that the final product aligns with user needs, preferences, and behaviours. The research involved observing business process flows, conducting competitor UI/UX analysis, creating user personas and journey maps, developing prototypes, and evaluating the design. The result is a website-based e-commerce prototype that enhances navigation, improves information search efficiency, and features a clean and readable interface. User testing and in-depth interviews indicate that the prototype improves business process clarity and efficiency, while also meeting user expectations regarding interaction control and perceived security.